2015
DOI: 10.1681/asn.2013121332
|View full text |Cite
|
Sign up to set email alerts
|

SREBP-1 Mediates Angiotensin II-Induced TGF-β1 Upregulation and Glomerular Fibrosis

Abstract: Angiotensin II is an important mediator of CKD of diverse etiology. A common pathologic feature of CKD is glomerular fibrosis, a central mediator of which is the profibrotic cytokine TGF-b. The mechanisms underlying the induction of TGF-b and matrix by angiotensin II are not completely understood. Recent studies showed that overexpression of the transcription factor SREBP-1 induces glomerular sclerosis and that angiotensin II can activate SREBP-1 in tubular cells. We thus studied whether SREBP-1 is activated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 50 publications
3
37
0
Order By: Relevance
“…However, although AEBSF treatment effectively diminished ATF6 cleavage, it is noteworthy that AEBSF is a non‐specific ATF6 inhibitor. S1P also facilitates cleavage of other proteins such as sterol regulatory element‐binding protein, which is associated with mesangial cell dysfunction (Wang et al, ). Although several recent studies have revealed that ATF6 activation induces apoptotic cell death in various cells (Han et al, ; Hirsch et al, ), further study is needed to reveal the precise role of ATF6 in mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, although AEBSF treatment effectively diminished ATF6 cleavage, it is noteworthy that AEBSF is a non‐specific ATF6 inhibitor. S1P also facilitates cleavage of other proteins such as sterol regulatory element‐binding protein, which is associated with mesangial cell dysfunction (Wang et al, ). Although several recent studies have revealed that ATF6 activation induces apoptotic cell death in various cells (Han et al, ; Hirsch et al, ), further study is needed to reveal the precise role of ATF6 in mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CHOPϪ/Ϫ mice are protected from ANG IIinduced NADPH oxidase activation, hypertension, and cardiovascular pathology (464). ANG II-induced ER stress exists downstream of the ADAM17/EGFR transactivation cascade (1034,1035) and stromal interaction molecule 1 (STIM1) induction (464), and upstream of cardiac (465) and renal TGF-␤ induction (1118), vascular apoptotic pathway (989), and brain SFO NF-B activation (1218). While these studies suggest that ER stress is vital for ANG II-induced signal transduction and pathologies, it remains elusive whether AT 1 R stimulation increases unfolded proteins in ER, or if so, how it happens.…”
Section: Endoplasmic Reticulummentioning
confidence: 99%
“…Moreover, EGFR transactivation by ANG II in renal proximal tubule appears critical for ANG II-induced renal TGF-␤ induction, epithelial cell-mesenchymal cell transition, and fibrosis (150,151). In addition to EGFR, a recent study demonstrated that ER stress-induced activation of a transcription factor sterol regulatory elementbinding protein-1 (SREBP-1) contributes to TGF-␤ induction and renal fibrosis in ANG II-infused mice (1118).…”
Section: Renal Fibrosis and Inflammationmentioning
confidence: 99%
“…De novo lipogenesis mediated by SREBP-1 has been described as a new mediator of TGF-β1 signaling pathway, thus its activation plays a key role in the progression of inflammation and glomerular fibrosis in this cell type under diabetic conditions [110][111][112].…”
Section: Lipotoxicity In Renal Cellsmentioning
confidence: 99%